Profile Metacognitive Scaffolding in Developing the Concept of Determinants to Enhance Mathematical Problem-Solving Skills of Low Ability Students - Awi, Awi; Sutamrin, Sutamrin; Naufal, Muhammad Ammar; Nasir, Norma; Hassan, Muhammad Nasiru (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The low ability of students to understand the concept of determinants and apply it in mathematical problem-solving remains a serious challenge, particularly among low-achieving learners. These difficulties are often linked to limited instructional variation, the dominance of procedural teaching, and insufficient opportunities for developing metacognitive awareness. This study therefore explores how metacognitive scaffolding can support low-achieving students in strengthening their conceptual understanding of determinants and improving problem-solving skills. The research employed a quantitative approach with a quasi-experimental design involving 30 tenth-grade students at MA Arifah Gowa, identified as low-achieving based on pretest results. Instruments included a mathematical problem-solving test, scaffolding observation sheets, and structured interviews. Data were collected through a pretest, classroom implementation of metacognitive scaffolding, observations, and a posttest. Findings revealed a significant improvement in problem-solving ability. The average score increased from 36.7 on the pretest to 74.8 on the posttest. Inferential analysis using a paired t-test confirmed the increase was statistically significant (t(29) = –12.34, p < 0.001), with a very large effect size (Cohen’s d = 1.80). These results highlight the importance of integrating metacognitive scaffolding into mathematics instruction as a means of fostering reflective thinking, enhancing student engagement, and strengthening higher-order thinking skills, particularly for low-achieving students. The findings align with the objectives of the Merdeka Curriculum, which emphasizes critical, reflective, and independent learning.